A Comparison of Image Quality and Radiation Exposure Between the Mini C-Arm and the Standard C-Arm. (November 2019) - van Rappard, Juliaan R. M.; Hummel, Willy A.; de Jong, Tijmen; Mouës, Chantal M.
Background: The use of intraoperative fluoroscopy has become mandatory in osseous hand surgery. Due to its overall practicality, the mini C-arm has gained popularity among hand surgeons over the standard C-arm. This study compares image quality and radiation exposure for patient and staff between the mini C-arm and the standard C-arm, both with flat panel technology.Methods: An observer-based subjective image quality study was performed using a contrast detail (CD) phantom. Five independent observers were asked to determine the smallest circles discernable to them. The results were plotted in a graph, forming a CD curve. From each curve, an image quality figure (IQF) was derived. A lower IQF equates to a better image quality. The patients' entrance skin dose was measured, and to obtain more information about the staff exposure dose, a perspex hand phantom was used. The scatter radiation was measured at various distances and angles relative to a central point on the detector.Results: The IQF was significantly lower for the mini C-arm resulting in a better image quality. The patients' entrance dose was 10 times higher for the mini C-arm as compared with the standard C-arm, and the scatter radiation threefold.Conclusions: Due to its improved image quality and overall practicality, the mini C-arm is recommended for hand surgical procedures. To ensure that the surgeons' radiation exposure is not exceeding the safety limits, monitoring radiation exposure using mini C-arms with flat panel technology during surgery should be done in a future clinical study.